Innovation-driven Economic Growth – How Hungary Will Be Home to Innovative Entrepreneurs and Enterprises - László Bódis; Ádám Kiss (Financial and Economic Review)
Productivity is significantly higher in countries that consistently spend at least 3 per cent of GDP on R&D, irrespective of economic cycles. Increasing productivity is necessary to boost the competitiveness of the economy and accordingly, significant growth in domestic R&D expenditure is essential. The challenges of the Hungarian RDI ecosystem have been properly identified, and the policy actions of recent years have put in place a strategic, institutional and funding framework to achieve these goals. In the long term, the objective is to create an ecosystem that is self-sustaining on a market basis, but where the state assumes a key role in designing the regulatory environment and the funding and supporting instruments. By systematically implementing the strategy outlined in this article, Hungary may be able to boost its economic performance through innovative, Hungarian-owned firms capable of producing high value-added products.